Sex Differences in Outcomes Following Percutaneous Coronary Intervention According to Age. (February 2016) - Epps, Kelly C.; Holper, Elizabeth M.; Selzer, Faith; Vlachos, Helen A.; Gualano, Sarah K.; Abbott, J. Dawn; Jacobs, Alice K.; Marroquin, Oscar C.; Naidu, Srihari S.; Groeneveld, Peter W.; Wilensky, Robert L.
Abstract : Background—: Women <50 years of age with coronary artery disease may represent a group at higher risk for recurrent ischemic events after percutaneous coronary intervention (PCI); however, no long-term, multicenter outcomes assessment exists in this population. Methods and Results—: Using the National Heart, Lung, and Blood Institute Dynamic Registry, we evaluated the association of sex and age on cardiovascular-related outcomes in10 963 patients (3797 women, 394 <50 years) undergoing PCI and followed for 5 years. Death, myocardial infarction, coronary artery bypass graft surgery, and repeat PCI were primary outcomes comprising major adverse cardiovascular events. Although procedural success rates were similar by sex, the cumulative rate of major adverse cardiovascular events at 1 year was higher in young women (27.8 versus 19.9%; P =0.003), driven largely by higher rates of repeat revascularizations for target vessel or target lesion failure (coronary artery bypass graft surgery: 8.9% versus 3.9%, P <0.001, adjusted hazard ratio 2.4, 95% confidence interval 1.5–4.0; PCI: 19.0% versus 13.0%, P =0.005, adjusted hazard ratio 1.6, 95% confidence interval 1.2–2.2). At 5 years, young women remained at higher risk for repeat procedures (coronary artery bypass graft surgery: 10.7% versus 6.8%, P =0.04, adjusted hazard ratio 1.71, 95% confidence interval 1.01–2.88; repeat PCI [target vessel]: 19.7% versus 11.8%, P =0.002, adjusted hazard ratio 1.8, 95% confidence interval 1.24–2.82). Compared with older women, younger women remained at increased risk of major adverse cardiovascular events, whereas all outcome rates were similar in older women and men. Conclusions—: Young women, despite having less severe angiographic coronary artery disease, have an increased risk of target vessel and target lesion failure. The causes of this difference deserve further investigation. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00005677. Abstract : Supplemental Digital Content is available in the text.